Introducing Statistics within a Gender Focal Point Strategy - Spiring, Fred (Advances in Social Sciences Research Journal, 2015)
The United Nations Development Strategy for Gender in Development Programme [1] relies heavily on two key components. The first is the strategy or problem solving technique often referred to as the Plan-Do-Check-Act (PDCA) cycle (or the PLANNING AND REVIEW CYCLES IMPLEMENTATION) and the second the Gender Focal Points. The PDCA cycle is a mechanism for planning, documenting, analyzing, implementing and verifying the impact of a plan or strategy and the GFPs are the resources critical to the implementation of the PDCA. This manuscript a) outlines the key components of the PDCA cycle along with tools associated with each of the four stages in the cycle and b) provides a gender based approach to integrating the concepts of statistics into the Gender Focal Point training regimen. A series of ten modules, each taking less than 120 minutes to present, have been developed using Microsoft Office’s [2] PowerPoint, Word and Excel. The ten modules were developed in conjunction with, and for use by, the Bureau of Women’s Affairs, Office of the Prime Minister, Government of Jamaica. The PowerPoint presentations, related datasets, questionnaires and supporting material are available from the author.